2007
DOI: 10.4049/jimmunol.179.6.3917
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Enhances Host Defense against Vaccinia Virus Infection Via a Mechanism Partly Involving IL-17

Abstract: To investigate roles of IL-23 in viral infection, we have engineered recombinant vaccinia virus (VV) expressing IL-12 (VV-IL-12) and expressing IL-23 (VV-IL-23). We found VV-IL-23 was less virulent in BALB/c mice than wild-type VV (VV-WT), indicating that IL-23 enhances resistance to VV. VV-specific CTL activity in VV-IL-23-infected mice was slightly higher than activity in VV-WT-inoculated mice, although antiviral Ab production and NK activity were not increased. IL-12/23p40-deficient mice survived the infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…28 We found that the rs11209026 variant in donor was associated with decreased risk of fungal infections and, IL-23/Th17 genetic variants in transplantation A Carvalho et al in patient, with improved OS, a finding consistent with the protective effects of IL-23 signaling attenuation in experimental aspergillosis. 25 The fact that donor rs11209026 also increased the risk of CMV infection, while consistent with the enhancing role of IL-23 of antiviral immunity, 39 indicates that fungal more than CMV infection may impact on OS in our cohort of patients. Although the variant could arguably influence OS by modifying the incidence of disease relapse or GVHD, a beneficial effect on relapse was only demonstrated in the univariate analysis and no effect on GVHD was found whatsoever.…”
Section: Discussionmentioning
confidence: 72%
“…28 We found that the rs11209026 variant in donor was associated with decreased risk of fungal infections and, IL-23/Th17 genetic variants in transplantation A Carvalho et al in patient, with improved OS, a finding consistent with the protective effects of IL-23 signaling attenuation in experimental aspergillosis. 25 The fact that donor rs11209026 also increased the risk of CMV infection, while consistent with the enhancing role of IL-23 of antiviral immunity, 39 indicates that fungal more than CMV infection may impact on OS in our cohort of patients. Although the variant could arguably influence OS by modifying the incidence of disease relapse or GVHD, a beneficial effect on relapse was only demonstrated in the univariate analysis and no effect on GVHD was found whatsoever.…”
Section: Discussionmentioning
confidence: 72%
“…with VV expressing IL-17 (VV-IL-17). In one study, VV-IL-17 was more virulent than WT virus (13), while in the other it was less virulent (14). The reason for the discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 82%
“…IL-17 is expressed in acute skin lesions of patients with AD and in their peripheral blood CD4 ϩ T cells (11,12). There is controversy as to whether IL-17 promotes or attenuates VV infection (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Previous studies have demonstrated that IL-17 plays a beneficial role in infections by various pathogens, including pulmonary Mycobacterium bovis, Klebsiella pneumonia and vaccinia virus. [9][10][11] The involvement of IL-17 in protection against influenza virus infection has also been indicated. Studies in vivo have demonstrated that IL-17 can protect mice against lethal infection with both A/Puerto Rico/8/ 34 (H1N1) and A/Alaska/6/77 (H3N2) influenza virus, which is accompanied by an enhanced early influx of neutrophils into the lung.…”
Section: Introductionmentioning
confidence: 99%